Differential Fractionation of Rare Earth Elements in Oxidized and Reduced Granitic Rocks: Implication for Heavy Rare Earth Enriched Ion Adsorption Mineralization. Issue 1 (20th December 2016) - Watanabe, Yasushi; Kon, Yoshiaki; Echigo, Takuya; Kamei, Atsushi
Abstract: Ion adsorption rare earth element (REE) deposits in southern China are the exclusive source of heavy REEs (HREEs) in the world, and this HREE‐enriched character of the deposits is inherited from the REE compositions of the underlying granitic rocks. Such HREE‐enriched rocks form from heavy fractionation of reduced granitic magmas. We explore why reduced granitic magmas are enriched in HREEs during the fractionation, based on the REE geochemistry of granitic rocks and abundance of REEs in their constituent minerals in the southwestern Japan arc of Cretaceous to Paleogene age. The compilation of the whole rock geochemistry and REE compositions of the granitic rocks of the Sanin (oxidized), Sanyo (reduced) and Ryoke (reduced) belts in the southwestern Japan arc indicates that: (i) light REEs (LREEs) decease with fractionation of the granitoids in the Sanin belt but this trend is not clear in the granitoids in the Sanyo belt and LREEs rather increase in the Ryoke granitoids; (ii) Eu decreases with fractionation in all the belts; and (iii) HREEs slightly, but steadily decrease in the Sanin belt but enrich significantly in the Sanyo and Ryoke belts with fractionation. Analytical results of REE concentrations by scanning electron microscope with energy dispersive X‐ray spectroscope and laser ablation‐inductively coupled plasma mass spectrometer in the constituent minerals in a granodiorite sample from the Sanin belt show a moderate concentration of REEs in hornblende (577 ppm) in addition to high concentrations in allanite (~20 %), britholite (~30 %), primary titanite (8922 ppm), apatite (4062 ppm), and zircon (1693 ppm). Because primary titanite and allanite are commonly present in the oxidized granitoids but not in the reduced ones, the REE depletion in the fractionated, oxidized granites is attributed to the crystallization of these minerals. In contrast, scarcity of these minerals in the reduced granitoids enriches REEs, in particular HREEs in the fractionated magmas, which finally precipitate REEs in the granites and pegmatites. Both positive, but different correlation ratios between the Nb and Dy concentrations in the granitoids of the Sanin and Sanyo‐Ryoke belts suggest that columbite–pyrochlore‐group and fergusonite‐group minerals are the major HREE host in the oxidized and reduced granites, respectively. Abstract : Compilation of geochemical data of the granitoids in the southwestern Japan arc indicates that the Sanin granitoids show prominent depletion of LREEs, whereas the Sanyo and Ryoke granitoids show progressive enrichment of HREEs with fractionation. The depletion and enrichment of REEs in the Sanin and Sanyo‐Ryoke granitoids is interpreted by the presence or absence of magmatic allanite and titanite in addition to hornblende, apatite and zircon, which incorporate REEs in their mineral structures.